The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1590/s0100-83582008000200014
|View full text |Cite
|
Sign up to set email alerts
|

Controle de papuã (Brachiaria plantaginea) em soja em função da dose e da época de aplicação do herbicida clethodim

Abstract: RESUMO -Herbicidas podem apresentar diferentes níveis de controle de plantas daninhas, em função de espécies presentes na área, estádio de desenvolvimento, dose do herbicida e condições de aplicação e de ambiente. Os objetivos deste trabalho foram investigar a possibilidade de uso de dose reduzida do herbicida graminicida clethodim, aplicado em pós-emergência, para controlar papuã em soja e quantificar a influência da época de aplicação do controle químico sobre variáveis agronômicas da cultura. O experimento … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
(21 reference statements)
1
2
0
8
Order By: Relevance
“…Regarding the variable PH, results showed that the resistant biotype was 43% higher compared to the susceptible at 140 DAE, with similar values between biotypes in evaluations carried out up to 60 DAE ( Figure 2B). PH is an important morphological characteristic that interferes with light competition (Fleck et al, 2008) due to the ability to prevent the shade, allowing plants a higher competitive ability with surrounding plants (Fleck et al, 2006). Similar results were observed in ryegrass biotypes resistant to the herbicides iodosulfuron-methyl and fluazifop, with a higher PH observed in evaluations from 60 DAE (Fraga et al, 2013;Mariani et al, 2016).…”
Section: Fitness Costsupporting
confidence: 65%
“…Regarding the variable PH, results showed that the resistant biotype was 43% higher compared to the susceptible at 140 DAE, with similar values between biotypes in evaluations carried out up to 60 DAE ( Figure 2B). PH is an important morphological characteristic that interferes with light competition (Fleck et al, 2008) due to the ability to prevent the shade, allowing plants a higher competitive ability with surrounding plants (Fleck et al, 2006). Similar results were observed in ryegrass biotypes resistant to the herbicides iodosulfuron-methyl and fluazifop, with a higher PH observed in evaluations from 60 DAE (Fraga et al, 2013;Mariani et al, 2016).…”
Section: Fitness Costsupporting
confidence: 65%
“…Nesse sentido, considera-se que o controle eficiente de plantas daninhas com o uso de herbicidas em pós-emergência depende, sobretudo, do estádio de desenvolvimento das plantas-alvo (Askew et al, 2000;Johnson & Hoverstad, 2002;Fleck et al, 2008). O emprego inadequado do glyphosate para controlar a trapoeraba, em seus diferentes estádios fenológicos, pode promover gasto desnecessário de capital e energia química (dose demasiadamente elevada nos estádios iniciais) ou mesmo resultar em baixo controle (estádios mais avançados).…”
Section: Introductionunclassified
“…This suggests that the plant developmental stage caused these results, since herbicides may have different levels of weed control, depending on the developmental stage, the herbicide dose, application and environment conditions (FLECK et al, 2008). Herbicide atrazina, carfentrazone, glyphosate, MSMA and paraquat herbicides, when when applied at stages 11 and 12 occasioned the lowest values for the plant height of C. benghalensis, showing efficacy in controlling this weed.…”
Section: Resultsmentioning
confidence: 98%